Preliminary evaluation of diploid banana hybrids for yield potential, male fertility and reaction to Radopholus similis - Krishnamoorthi, V.=700 1 Kumar, N.
(En, Fr, Es)
ilus., 17 ref.
Keywords: BANANO; HIBRIDOS SOMATICOS; PARTENOCARPIA; RENDIMIENTO; CALIDAD; FRUTO; RESISTENCIA A LAS PLAGAS; RADOPHOLUS SIMILUS; ITALIA